Involvement of Peripheral Opioid Receptors in the Realization of Food Motivation Into Eating Behavior - Sudakov, Sergey; Bogdanova, Natalia (Frontiers in Behavioral Neuroscience, 2021)
The involvement of gastric opioid receptors in the mechanisms of eating behavior is still unclear. The aim of this work was to study the role of gastric mu and delta opioid receptors in the realization of food motivation in conditions of different energy costs for eating behavior. Experiments were performed under a between-sessions progressive ratio schedule of reinforcement in food-deprived rats. The level of food motivation was calculated using a self-developed method. Food intake, motor activity, and metabolic rate were recorded in fed and hungry animals. Results showed that intragastric administration of the mu opioid receptor agonist DAMGO led to an increase in the level of food motivation in the light variant of operant feeding behaviors. Food consumption did not change. At high costs for feeding behavior, the administration of DAMGO did not alter food motivation; however, food consumption and motor activity were reduced. Intragastric administration of the delta opioid receptor agonist DADLE did not lead to changes in the level of food motivation and physical activity, but inhibition of feeding behavior was observed in all reinforcement schedules. Three regulatory pathways of eating behavior in difficult food conditions by gastric opioid receptors are proposed: environmental - inhibitory afferentations and suppression of the realization of food motivation into behavior; homeostatic - inhibitory action on food motivation; and rewarding - suppression of the anticipatory reinforcement.